ENHANCING MSME PERFORMANCE THROUGH IMPROVEMENTS IN ACCOUNTING INFORMATION SYSTEMS: A COMPARATIVE STUDY OF INDONESIA AND MALAYSIA - Anggadini, Sri Dewi; Saepudin, Asep; Azis, Fairuzyah Rofifah; Surtikanti, Surtikanti; Fahrana, Egi; Damayanti, Sari (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to analyze and compare the quality of accounting information systems implemented in Micro, Small, and Medium Enterprises (MSMEs) between Indonesia and Malaysia, to enhance performance effectiveness in these entities. A descriptive analysis is employed based on a qualitative approach to assessing the quality of accounting information systems. Data analysis involves summarizing data, documents, literature reviews, and previous research. The findings of this study align with previous research, indicating that implementing a high-quality accounting information system positively correlates with the effectiveness of MSME performance in both Indonesia and Malaysia. In summary, this research demonstrates that MSMEs that have adopted an accounting information system exhibit enhanced performance, particularly in decision-making processes, internal control, and the quality of financial reporting. The implications of this research extend to MSMEs, academic and non-academic literature, as well as future studies